1973
DOI: 10.1084/jem.137.4.893
|View full text |Cite
|
Sign up to set email alerts
|

Acute Destruction by Humoral Antibody of Rat Skin Grafted to Mice

Abstract: We have described briefly the acute destruction of rat skin xenografts after injections of their hosts with antisera specifically reactive with graft antigens (1). The rat skin had been grafted to mice whose immune responses were suppressed by removal of the thymus and treatment with rabbit antimouse lymphocyte serum. When these xenografts had healed completely into their beds and could be fully expected to survive for one or more additional weeks, the mice were injected with antirat serum that had been prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Xenotransplants are also rejected normally in Xid mice (51), and BALB/C skin is rejected normally in agammaglobulinemic B10.BR mice treated chronically with anti-IgM serum to deplete B cells (52). Reduced allograft-specific Ab quantities following B cell depletion did not appear to affect skin graft (Figure 5A–B) or cardiac allograft (Figure 4) rejection, even though the addition of exogenous allograft-specific Ab is capable of inducing skin graft destruction (53, 54). Further, allograft-specific Abs can cause pathological lesions in mouse cardiac allografts (55) and allograft rejection in immunosuppressed mice (11, 15, 16).…”
Section: Discussionmentioning
confidence: 96%
“…Xenotransplants are also rejected normally in Xid mice (51), and BALB/C skin is rejected normally in agammaglobulinemic B10.BR mice treated chronically with anti-IgM serum to deplete B cells (52). Reduced allograft-specific Ab quantities following B cell depletion did not appear to affect skin graft (Figure 5A–B) or cardiac allograft (Figure 4) rejection, even though the addition of exogenous allograft-specific Ab is capable of inducing skin graft destruction (53, 54). Further, allograft-specific Abs can cause pathological lesions in mouse cardiac allografts (55) and allograft rejection in immunosuppressed mice (11, 15, 16).…”
Section: Discussionmentioning
confidence: 96%
“…As mentioned in the previous section, Winn and co-workers conducted a series of experiments with mice receiving rat skin grafts [4]. Rejection was shown to be dependent on complement, as judged by the inability of non-complement fixing antibodies or F(ab′) 2 fragments to mediate rejection, prevention by depletion of complement by cobra venom factor and resistance to rejection in C5 deficient recipients.…”
Section: Acute Amr: Experimental Studiesmentioning
confidence: 99%
“…Therefore, antibody was not thought to mediate rejection. In contrast, Winn and co-workers showed that if rat skin grafts were allowed to heal in over 2 weeks in immunosuppressed mice, grafts became highly susceptible to acute rejection by adoptive transfer of mouse anti-rat serum with immediate effects evident 10 min after serum administration and total graft loss in 1–2 days [4]. Gerlag and co-workers confirmed the sensitivity of healed in skin grafts to donor specific antiserum in analogous studies in mouse skin allografts [5].…”
Section: Introductionmentioning
confidence: 99%
“…2). The reason most likely is a great individual variability in mobilising the different mediator systems which are triggered by the antigen antibody reaction at the glomerular basement membrane (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%